An Experimental Study On Flexural & Tensile Strength Of Concrete By Using Sugarcane Baggase Ash& Steel Fiber - Mr. Shrikant s solanke , Dr. P. Y. Pawade (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Generally the concrete is weak in tensile as well as flexural strength which are some basic strength properties of any structure. Steel fiber can be potentially used in the concrete to improve its structural strength. Use of steel fiber in the concrete will also reduce the steel reinforcement requirement at later stage. Concrete was prepared in the present research work in which sugarcane bagasse ash was used to substitute cement to minimize cement use and thereby reduce construction costs. In this work concrete cubes were casted in various proportions of SCBA like 5%, 10%, 15%, and 20%. This combination was further enhanced by adding steel fiber by volume in percentages like 0.5%, 1%, and 1.5%. The cubes were prepared using this combination and tested at different curing ages, such as 7-days, 28-days, 56-days and 90-days. At such ages, concrete properties such as compressive strength, flexural strength and split tensile strength were analyze